Hemodynamic effect of calcifed plaque on blood flow in carotid artery disease: A preliminary study - Hemodynamic effect of calcified plaque - Sun, Zhonghua; Mwipatayi, Bibombe; Chaichana, Thanapong; Ng, Curtise (My University, 2009)
The purpose of the study is to investigate the hemodynamic effect of calcified carotid plaque on blood flow in patients diagnosed with carotid artery disease. Two carotid artery models were generated based on a sample patient data, with normal and calcified carotid artery appearances. Circular calcified carotid plaque was found at the carotid bifurcation based on 3D computed tomography images. A computational fluid dynamics was performed to analyze the changes of blood flow in different situations. Our results showed that apparent turbulence was found in the diastolic phase at the carotid bifurcation in normal carotid artery geometry. In the presence of the calcified plaque, the flow velocity was increased to some extent, indicating the effect of plaque on hemodynamic changes. Wall shear stress was noticed to decrease at the aortic branches, and this indicates the potential risk of developing stenosis at this area. Our preliminary study demonstrates fluid structure interaction between calcified plaque and artery in terms of flow changes and wall shear stress. ©2009 IEEE.
Keywords: Blood flow; Calcification; Carotid artery disease; Computed tomography; Model